Acceleration of productivism and co-optation of subjectivity as aspects of the relationship between work and technology - Oliveira, Lorena Esteves de; Oliveira, Eloiza da Silva Gomes de (Seven Editora, 2023)
This theoretical essay aims to promote a critical debate on the relationship of technology with organizations, focusing on the subjective aspects that result from the acceleration of work. To this end, this study was divided into two moments, one first, which dealt with the co-optation of the subjectivity that adheres the subject to a capitalist ideology in which the objective of his work ceases to be personal fulfillment to become the realization of organizational profit. The worker becomes the subject of high performance and positivity. In the second moment, the acceleration of work was treated, a fact that, having been the subjectivity of the subject duly sequestered, he launches himself into an increasingly flexible work, more present in all moments of life, where even the sleep barrier is not respected. It is concluded that there is a need for a continuous study on the relations between work and technology in order to safeguard the subjectivity of the subject of the precariousness of work. DOI:https://doi.org/10.56238/alookdevelopv1-097